KINETICS OF CONVECTIVE CRYSTAL DISSOLUTION AND MELTING, WITH APPLICATIONS TO METHANE HYDRATE DISSOLUTION AND DISSOCIATION IN SEAWATER - Zhang Y.; Xu Z. (My University, 2003)
Large quantities of methane hydrate are present in marine sediment. When methane hydrate is exposed or released to seawater, it dissolves in seawater or dissociates into methane gas and water. There was some confusion in the literature about the kinetics of these processes. It is critical to realize that dissolution and dissociation are two different processes. Dissolution is due to instability in the presence of seawater (similar to dissolution of NaCl in water) and is controlled by mass transfer. Dissociation is due to inherent instability (similar to melting of ice) with or without water (although presence of warm water may increase the dissociation rate). Dissociation of methane hydrate into gas and water is similar to ice melting and is controlled by heat transfer. Hence dissolution is relatively slow and dissociation is rapid. In this work, we extend previous theory on convective crystal dissolution and melting to greater Reynolds numbers. We carry out laboratory experiments on the dissolution and descent of NaCl, KCl, NaBr and KBr in water to verify the applicability of our theory. We then apply our models as well as previous ones to estimate methane hydrate dissolution and dissociation rates for several cases, including dissolution of exposed methane hydrate floor, dissolution and dissociation of hydrate as it rises through seawater. The results show: (i) convective dissolution rate of exposed hydrate floor is of the order 0.07 m/yr; (ii) convective dissolution rate of a rising hydrate crystal is 0.2-0.3 μm/s and a crystal of 5 mm radius is able to survive the rise through an 1800 m seawater column; and (iii) convective dissociation rate is high and depends on the difference between the ambient water temperature and the equilibrium dissociation temperature of hydrate. Starting from a depth when hydrate just reaches dissociation instability, a hydrate sphere of 5 mm radius would survive only a 47 m water column. Because hydrate is unstable in the surface ocean and would undergo rapid dissociation, only very large hydrate chunks (greater than about 0.09 m radius) would be able to survive a 530 m surface water column.
Keywords: SHERWOOD NUMBER; CRYSTAL DISSOLUTION; METHANE HYDRATE DISSOCIATION